Latest Oligocene to early middle Miocene quantitative calcareous nannofossil biostratigraphy in the Mediterranean region - FORNACIARI, ELIANA; RIO, DOMENICO (Micropaleontology Press, 1996)
The distribution patterns of selected calcareous nannofossils were investigated by means of quantitative methods in uppermost Oligocene to lower middle Miocene sediments from onland stratigraphic sections in Italy. Our goal was to test the reliability, in the Mediterranean region, of the biohorizons used in the standard zonations of Martini (1971) and Bukry (1973, 1975) and of others recently proposed in the literature. Biostratigraphic reliability was evaluated by considering the mode of occurrence of single biohorizons and their potential for correlation among distant and various facies sections. Several conventionally used boundary definition biohorizons (Discoaster druggii FO, Triquetrorhabdulus carinatus LO, Helicosphaera recta LO, Cyclicargolithus abisectus acme end) are considered as not reliable. They are therefore of limited use for solving the geological problems of the region. However, by using distinct changes in the distribution patterns of calcareous nannofossils, like first common and continuous occurrence (FCO), last common and continuous occurrence (LCO), and acme end (AE), besides classical first occurrence (FO) and last occurrence (LO), at least 13 biohorizons can be consistently correlated among the studied sections. We established a set of 11 regional biostratigraphic zones and subzones, which are also recognized in poorly fossiliferous turbiditic successions. The average time resolution of the proposed zonal system is less than 1 m.y., which can be substantially improved by integrating calcareous nannofossil and planktonic foraminifera biostratigraphies. The correlation of the proposed zonal system to the Standard Chronostratigraphic Scale is discussed. The Oligocene/Miocene and Aquitanian/Burdigalian boundaries lack formal definition and are currently recognized by different criteria. We propose that, for the time being, these boundaries should be recognized by buffer intervals which include several calcareous nannofossil biohorizons. A new Sphenolithus species is described, Sphenolithus ...